Earning while Learning: A Model of Fine Arts Education - Sharma, Yam Prasad (Journal of Fine Arts Campus, 2024)
Fine arts students have the potential for earning while learning. The genres of fine arts like painting, sculpture, graphic design, music and dance not only have aesthetic values but also provide technical skills to the students. The acquired skills can be immediately used in the field of making portraits, landscapes, book illustration, package design, product design, logo design, garden design, interior decoration, architecture, museum, art gallery, advertisement, theatre, musical bands and concerts, schools, art research and criticism, art history and so on. There is the lack of skilled human resource in these fields. Fine arts students can work part time or full time in these areas. When they learn basic techniques and skills of arts in the early years, they can immediately work. This supports for their livelihood and education. Similarly, they can be financially independent. Furthermore, the earning while learning contributes for smooth transition of students from education to employment. The universities should manage the time, schedule and teaching learning activities in such a way that a student can work while studying. The achievement of this goal brings the win-win situation to the students, teachers, campuses, universities, parents and the nation.